Collaborative Governance in the Effort to Prevent the Criminal Action of the Financing of Terrorism Through Freezing of Individual and Entity Assets - Guntur Wijaya Kesuma; Surya Nita; Zora A. Sukabdi (Budapest International Research and Critics University, 2022)
UN Security Council Resolutions 1267 (1999) and 1373 (2001), call on all countries in the world to provide financial sanctions against Al-Qaeda and the Taliban, including citizens of every country affiliated with and assisting Al-Qaeda and the Taliban. In 2012, the FATF once more classified Indonesia as a